Peran Koordinasi Bappeda dalam Meningkatkan Pembangunan Masyarakat (Studi pada Bappeda dan Tim Koordinasi Pengelolaan Program dan Kegiatan Tanggung Jawab Sosial dan Lingkungan Perusahaan (TJSLP) di 3 Kecamatan Kabupaten Sidoarjo) - Zaskya Rizky Karundini (Jurnal Administrasi Publik, 2014)
Abstract: The Role of Bappeda Coordination In Increasing Community Development (The study of Bappeda and Tim Koordinasi Pengelolaan Program dan Kegiatan TJSLP in the 3 sub district of Kabupaten Sidoarjo). Bappeda as the compiler and implementer of development in the region, conduct the coordination role in order to implement itâ€™s duty and function in developments, one of them is Bappeda in Sidoarjo regency with the Tim Koordinasi Pengelolaan Program dan Kegiatan TJSLP which is formed by Bappeda. Bappeda as the compiler of coordination team implemented its role as a planner, coordinator, and evaluator. But the coordination between Bappeda and Tim Koordinasi which is analyzed in this study did not work effectively and appropriate with the community development values. The supporting factors of coordination between Bappeda and sub district coordination team are the presence of the members who have been implement the tasks and its function and the existence of informal relationship beside a formal relationship. While the inhibiting factors are the lack of communication and integration between the members, funding obstacle, and the flurry of the team members. Â  Keywords: role, coordination, Bappeda, community development, Management Coordination Program Team and Corporate Social Responsibility (CSR), sub districtÂ